THE MECHANISM OF FORMATION OF THE BAIKAL BASIN - Artyushkov E.V.; Letnikov F.A.; Ruzhich V.V. (My University, 1990)
The Baikal is a deep long and narrow basin in East Siberia which follows a huge fault zone adjoining the Siberian Platform. The basin was formed by rapid subsidence of continental crust during the pas 3–4 Ma. It is bounded by normal faults which indicate extension of the crust during the subsidence. According to seismic reflection profiling data, the intensity of extension is not large (3–7%). It is much smaller than the thinning of the crystalline crust under the basin (up to 38%). The thinning and crustal subsidence can be explained by the transformation of gabbro in the lower crust into dense garnet granulites. The latter rocks (with ) are still located under the remnant part of the crust. Rapid transformation took place due to an inflow of catalyzing fluid along the fault zone from the asthenospheric upwelling. This upwelling, which is at a depth of 80–90 km, caused a general uplift of a broad area in the south of East Siberia.